1997
DOI: 10.1007/bf02113504
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 diagnosis in pregnant women — quantification of IgG antibody levels (IU/ml) with reference to the international parvovirus B19 standard serum

Abstract: On the basis of the results of a collaborative study the Expert Committee on Biological Standardisation of the World Health Organisation has issued an international standard (IS) serum for parvovirus B19 IgG antibody (NIBSC 93/724). In this study this IS was used to calibrate an in-house standard serum for reporting the results of parvovirus B19 IgG testing in IU/ml. The IgG titre distribution in 939 pregnant women was determined. These samples were sent to the laboratory for determining the immune status to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The B19 infections were observed to affect usually children in all the world. This previous experience was demonstrated by presence of seropositivity for anti-B19 IgG from 63% (Searle et al 1997) to 80% (Cassinotti et al 1997) in adults.…”
mentioning
confidence: 72%
“…The B19 infections were observed to affect usually children in all the world. This previous experience was demonstrated by presence of seropositivity for anti-B19 IgG from 63% (Searle et al 1997) to 80% (Cassinotti et al 1997) in adults.…”
mentioning
confidence: 72%
“…In a similar study carried out in Europe using the parvovirus B19 IgM immunoassay, a population of Irish blood donors gave a parvovirus B19 IgM seroprevalence rate of 1/417 (0.24%) or 0.72% if two equivocal test results were included as reactives (data not shown). In addition, Searle et al, (1997) have observed a parvovirus B19 IgM seroprevalence of 2.34% in cohort of 939 German women following exposure to, or suspicion of infection with, parvovirus B19 during pregnancy. Further studies using a larger population cohort may help clarify the significance of the observed difference in parvovirus B19 IgM seropositivity between the two groups in the present report.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed many other viral infections, particularly rubella, induce symptoms similar to parvovirus B19 (Thomas et al, 1999;Turner, 1999). However, for optimal assessment of the likelihood of infection and determination of the risk of fetal hydrops in pregnancy, serological analysis should also determine the parvovirus B19 IgG status of the patient and follow up specimens should be drawn from the patient, where possible (Searle et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In S2, IgM antibodies were detected for more than 90 weeks, whereas in all others, they were lost between weeks 15 and 35. From the second week, IgG levels were raised and maintained above 6 IU/ml (23). In S2 and S5, B19 DNA was detected in PBMC throughout the entire follow-up, while this was lost between weeks 13 and 41 in the other individuals.…”
Section: Staining (Ics) (18) Pbmc Was Depleted Of Cd8mentioning
confidence: 96%